2020
DOI: 10.22271/chemi.2020.v8.i4e.9706
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fungicides against stem rot of capsicum caused by Sclerotium rolfsii Sacc

Abstract: Stem rot (Sclerotium rolfsii Sacc.) of capsicum which is also called as collar rot or southern blight is one of the serious diseases in capsicum that severely brings down the yield in all the major capsicum growing areas in Karnataka. Among the several management practices, managing the disease with fungicides is the most effective means. In the present investigation twelve fungicides that included three systemic, six combi products and three contact fungicides were evaluated against S. rolfsii in vitro. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…The in vitro testing of fungicides gives valuable data on their ability to effectively combat a pathogen in the shortest period of time, and as a result, These results are in agreement with the findings of other studies [25][26][27] who reported that "the combo products containing triazoles viz., Avatar, Merger and Nativo were highly inhibitive to the growth of S. rolfsii". Similarly the studies by [28][29][30][31] who observed that "100 per cent inhibition of mycelial growth by these combi fungicides against S. rolfsii Sacc. from different crop system" [32].…”
Section: Discussionsupporting
confidence: 53%
“…The in vitro testing of fungicides gives valuable data on their ability to effectively combat a pathogen in the shortest period of time, and as a result, These results are in agreement with the findings of other studies [25][26][27] who reported that "the combo products containing triazoles viz., Avatar, Merger and Nativo were highly inhibitive to the growth of S. rolfsii". Similarly the studies by [28][29][30][31] who observed that "100 per cent inhibition of mycelial growth by these combi fungicides against S. rolfsii Sacc. from different crop system" [32].…”
Section: Discussionsupporting
confidence: 53%
“…According to Mahato et al (2014 S. rolfsii and had no influence on mycelial growth. Arunasri et al (2011), Manu et al (2012, Deepthi (2014), Suneeta et al (2017), Shirsole et al (2019) and Sahana et al (2020). Sclerotium rolfsii grows in all pH tested, 4.0 to 7.0.…”
Section: Resultsmentioning
confidence: 92%